Carrying Capacity of a Tourist Destination: Case Study of Saung Angklung Udjo as Cultural Heritage Tourism Destination in Indonesia - Pratiwi, A (KnE Social Sciences, 2018)
The research on the ‘The Carrying Capacity of a Tourist Destination: Case Study of Saung Angklung Udjo as Cultural Heritage Tourism Destination in Indonesia’ was conducted between May and August 2013. This study aims to understand the general preservation undertakings conducted by Saung Angklung Udjo as a tourist destination. In particular, the purpose of this study was (1) to determine the implementation of sustainable tourism to Saung Angklung Udjo, (2) to assess the implementation of the physical carrying-capacity calculations at Saung Angklung Udjo, and (3) to determine the preservation of angklung as intangible cultural heritage. This study used a qualitative research technique of data collection through direct observation in the area, conducted interviews, questionnaire, and examination of documents. Informants in this study consist of General Manager and Facilities of Saung Angklung Udjo, while respondents for this study were 16 tourists comprising 11 domestic tourists and 5 foreign tourists. The results showed that: (1) Saung Angklung Udjo implement constructive measures for new installations and means of monitoring facilities in service to preserve and promote the tourist attractions. By connecting the cultural heritage preservation improvement and optimization of existing infrastructure by local professional actors, (2) to promote long-term economic prosperity and improve the present generation without compromising the ability of nature, society and the economy to raise the welfare of future generations, and (3) cultural identity as a cultural heritage that can be developed into economic capital and assets in order to make a significant contribution to the welfare of society in development while maintaining cultural values and local wisdom as its hallmark. Keywords: carrying capacity, cultural heritage, local community, sustainability, Saung Angklung Udjo